Artificial Intelligence and Its Applications - Vishalagoud S Patil (AG Volumes, 2022)
Artificial intelligence is the art and science of developing machines running on intelligent algorithms that make them capable of thinking, acting and learning like human beings. A main drive of AI is in the improvement of computer functions associated with human intelligence. This chapter discusses on areas of AI, advantages and disadvantages of AI and its application in the real world.